Analisis Perencanaan Pajak Dalam Pemilihan Pemajakan UMKM Antara Peraturan Pemerintah Nomor 23 Tahun 2018 Dibandingkan Pasal 31E Undang-Undang Pajak Penghasilan Terhadap Efisiensi Pembayaran Pajak Penghasilan Badan Pada PT. KOP Mandiri Sejahtera Tahun 2020 - Abriyaldi Abriyaldi; Chairil Anwar Pohan (Jurnal Ilmu Administrasi Publik, 2023)
Taxation is the main source  of state revenue because  it accounts  for about  78% of state revenue (realization  in 2020).  One  of  the  government's   policies  to  increase revenue  is  to  provide  incentives  for  MSME businesses through Government Regulation Number 23 of 2018. This regulation applies to MSMEs that have a gross turnover of up  to  Rp. 4,800,000,000  per  year.  This  study  aims  to determine the comparison of corporate  income tax payments of PT.  Kop Mandiri  Sejahtera  in 2020  using Government Regulation Number 23 of 2018 compared to Article 31E of the Income Tax Law. The analysis is carried out related to tax planning carried  out by the company in the  context  of tax  payment  efficiency. This study  used descriptive qualitative method. The data collection of this research  was done by using interview, documentation and observation   techniques.   The  results   showed  that   the policies taken by PT. Kop Mandiri Sejahtera, namely using Government Regulation Number 23 of 2018 in calculating the company's corporate  income tax obligations  in 2020 resulting in higher income tax payments compared to the use of Article 31E of the PPh Law.